The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1007/s00442-007-0713-3
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to rust fungi in Lolium perenne depends on within-species variation and performance of the host species in grasslands of different plant diversity

Abstract: The hypothesis that plant species diversity and genetic variation of the host species decrease the severity of plant diseases is supported by studies of agricultural systems, but experimental evidence from more complex systems is scarce. In an experiment with grassland communities of varying species richness (1, 2, 4, 8, 16, and 60 species) and functional group richness (1, 2, 3, and 4 functional groups), we used different cultivars of Lolium perenne (perennial ryegrass) to study effects of biodiversity and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 46 publications
4
30
1
Order By: Relevance
“…Strikingly similar results have been found in experimental studies in which fungal pathogen prevalence in herbaceous plants decreased with increasing plant species diversity [11], [13]. Experimental studies in other systems, combined with longer-term studies and models, will elucidate the degree to which this protective effect of high biological diversity is general.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Strikingly similar results have been found in experimental studies in which fungal pathogen prevalence in herbaceous plants decreased with increasing plant species diversity [11], [13]. Experimental studies in other systems, combined with longer-term studies and models, will elucidate the degree to which this protective effect of high biological diversity is general.…”
Section: Discussionsupporting
confidence: 75%
“…In both cases, high diversity is correlated with low disease risk or prevalence. With the exception of fungal diseases of plants [11][13] experimental assessments of the role of species diversity in disease dynamics are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…3). The species diversity of a community can either reduce or intensify disease severity (Keesing et al, 2006), but empirical studies have shown that diversity generally reduces disease severity (Keesing et al, 2010), a relationship that has been observed in wild plant communities (Roscher et al, 2007;Haas et al, 2011). Therefore, heterogeneity of land-use might affect mortality by increasing the species diversity of the surrounding area.…”
Section: Landscape Factors Affecting Mortalitymentioning
confidence: 97%
“…The stand-level density of host trees is known to influence the occurrence of Japanese oak wilt (Yamasaki and Sakimoto, 2009;Yamasaki et al, 2014). In addition, the existence of non-host trees could potentially affect disease occurrence (Roscher et al, 2007;Haas et al, 2011). Therefore, the BAs and number of individuals were summed for each of three host species (Q. crispula, Q. serrata, and F. crenata), and each of the three groups of non-host species (C. japonica, other broad-leaved and coniferous species), then used in the analyses.…”
Section: Field Observations At the Stand Levelmentioning
confidence: 99%
“…During the hot Mediterranean summers, they are in dormancy and basidiospores germinate during the winter rainy season (Kolmer 2005). Roscher et al (2007) reports that both pathogens produce sporangia, which can be seen especially in late summer and autumn. In our monitoring, combined infections (Puccinia graminis + Puccinia coronata) were the most frequent at Deschampsia caespitosa (L.) P.B.…”
Section: Discussionmentioning
confidence: 99%